Highly efficient asymmetric (diphenylphosphino)benzene‐based chromium catalysts for selective ethylene trimerization. (4th October 2022) - Ma, Jing; Fan, Haonan; Hao, Biaobiao; Jiang, Tao
Abstract : The corresponding Cr(III) catalysts (1–6 ) based on asymmetric (diphenylphosphino)benzene‐type L 1 –L 6 ligands have been explored for ethylene selective trimerization. It is observed that the structure of the complexes has an obvious influence on their catalytic performance for ethylene selective oligomerization. All the 1–6 precatalysts may offer selective ethylene trimerization systems, and their catalytic performance is greatly influenced by the reaction conditions. The precatalyst 2, bearing diisopropylphosphanyl substituent, may exhibit the remarkably high catalytic activity of 9.83 × 10 7 g/(molCr·h) with 90.4% C6 selectivity under suitable conditions. Single crystal X‐ray analysis showed that the alkyl/alkylaminophosphanyl of the ligands may efficaciously tune the catalyst structure and thus influence the oligomerization activity and product selectivity. Abstract :